IDENTIFIKASI EFEKTIVITAS PROSES PEMBELAJARAN MATAKULIAH ORGANISASI DAN ARSITEKTUR KOMPUTER DI STMIK NURDIN HAMZAH - Faiza Rini (JURNAL AKADEMIKA)
increase the effectiveness of the learning process in Computer Organization and Architecture course the authors ampu, to see how far the effectiveness and gaps in the learning process, and try to fix the problem by knowing the cause, so that what is desired from the learning objectives achieved, casual description of the learning problems can be analyzed with the fishbone diagram approach of questionnaire data instrument could spread to the learning process of students.